PENGARUH PENGELOLAAN BARANG MILIK DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA PADANG - Anshari Anshari; Efrizal Syofyan (Jurnal Riset Manajemen Bisnis dan Publik, 2016)
The purposeof this researchis to find out the influence of asset management  of  Governmentof Padang, its impact on quality offinancial report of the Governmentof Padang. The conclusion are Inventory of assets, legal audit assessment of assets and supervision  have positivly and significant impacton the quality offinancial report ofthe Governmentof Padang. Keyword: assets management, inventory, legal audit, assessment, controlling, quality of financial report.